Agroforestry for a Changing Climate - International Institute of Rural Reconstruction (2019)
The brief tackles the role of agroforestry in achieving food and nutritional security, climate change mitigation and environmental resilience. The publication is based on the small agroforestry project in Guinayangan Climate-Smart Village in Quezon Province, Philippines implemented by the International Institute of Rural Reconstruction and CCAFS Southeast Asia.